Innovative Agri-Startups: Boosting the Future of Agriculture in India - Yadav, Shiv Shankar; Singh, Sukhjinder; Verma, Manish (AMC Indian Journal of Entrepreneurship, 2022)
Agriculture is regarded as India’s economic backbone. It contributes significantly to national income, employment, and foreign exchange earnings. The commitment of agriculture and its related divisions to outside trade benefits was diminished from 44.24% in 1960â€“1961 to 14.34% in 2020-2021. Despite the decay in its share of national yield and business, farming and related segments proceed to be the essential root of pay for over half of Indiaâ€™s population. Agri-startups and agribusinesses are shaping noteworthy numbers around the nation to hold up rural esteem expansion exercises and give innovative advances, products, and administrations for advancement of agriculture . The scaling-up of agri-startups is being encouraged by the government of India. Startup India, Rashtriya Krishi Vikas Yojana â€“ Remunerative Approaches for Agricultural and Allied Sector Rejuvenation (RKVY-RAFTAAR), agri-entrepreneurship, development component, startup incubation, and development are fiscally bolstered by Department of Biotehnology (DBT), Department of Science and Technology (DST), National Bank for Agriculture and Rural Development (NABARD) and National Institution for Transforming India (NITI) Aayog. The purpose of this paper was to examine the influence of innovative agri-startups in assisting farmers and entrepreneurs in meeting their demands.